2021
DOI: 10.1002/ptr.7253
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of tanshinone IIA and puerarin for pulmonary fibrosis via targeting IL6‐JAK2‐STAT3/STAT1 signaling pathways

Abstract: Efficient therapy of idiopathic pulmonary fibrosis (IPF) is still a major challenge. The current studies with single-target drug therapy are the pessimistic approaches due to the complex characteristics of IPF. Here, a combination therapy of Tanshinone IIA and Puerarin for IPF was proposed to alleviate IPF due to their antiinflammatory and anti-fibrotic effects. In vivo, the combination therapy could significantly attenuate the area of ground glass opacification that was presented by 85% percentile density sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Through the semi-quantification of micro-CT images obtained from 66 mice, we observed that the distribution pattern of fibrosis was predominantly located in the mid-to upper- and dorso-centric regions of the lungs 21 days after bleomycin administration, consistent with prior published studies [ [4] , [5] , [6] , 8 , [13] , [14] , [15] , [16] , [17] ]. This distribution pattern may be attributable to the fact that bleomycin primarily settles in the mid-to upper-lungs along with the airflow of breathing.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Through the semi-quantification of micro-CT images obtained from 66 mice, we observed that the distribution pattern of fibrosis was predominantly located in the mid-to upper- and dorso-centric regions of the lungs 21 days after bleomycin administration, consistent with prior published studies [ [4] , [5] , [6] , 8 , [13] , [14] , [15] , [16] , [17] ]. This distribution pattern may be attributable to the fact that bleomycin primarily settles in the mid-to upper-lungs along with the airflow of breathing.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the development of micro-CT quantification methods for BIPF mouse models over the past decade [ 4 ], this technique has not been routinely employed for monitoring changes in lung fibrosis. Typically, micro-CT is used only at the endpoint of a study [ [5] , [6] , [7] , [8] ], which makes it challenging to ascertain whether the mice had comparable degrees of fibrosis at the study's start before any therapeutic interventions (no early than 7–10 days post-bleomycin) [ 9 ]. This is largely due to the fact that manual tools for micro-CT image analysis are time-consuming and labor-intensive [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sulforaphane, dihydroartemisinin, melatonin and ginkgo biloba extract have been found to reduce oxidative stress to exert anti-pulmonary-fibrosis effects [99][100][101][102][103]. Similarly, the total extract of Yupingfeng and the combination of tan IIA and puerarin can exert antifibrotic effects by regulating the PI3K/AKT/mTOR signaling pathway and JAK/STAT signaling pathway [104][105][106]. As for regulating signaling pathways related to EMT, asiatic acid and oridonin inhibit the expression of TGF-β1 in lung tissue, accompanied by a decrease in Col-I, Col-III, α-SMA and TIMP-1, as well as inactivation of Smads and ERK1/2 [107,108].…”
Section: Antifibrosis Treatment Drugs For Ipfmentioning
confidence: 99%
“…It has good effects of anti-inflammation, anti-infection and regulating immunity. Some earlier studies have investigated the effects of TSA on the proliferation reduction dose-dependently index of abnormally proliferating fibroblasts in HS ( Xue et al, 2021 ). However, as a kind of fat-soluble strong phenanthrene quinone compound, TSA is difficult to penetrate the active epidermis of human body.…”
Section: Introductionmentioning
confidence: 99%